Cervical spinal degenerative disease in multiple sclerosis. (5th May 2021) - Chhugani, Simran; Agarwal, Nivedita; Sheikh, Faraz; Borca, Florina; Spanoulis, Aginor; Galea, Ian
Abstract: Background and purpose: Root and cord irritation from cervical spinal degenerative disease (SDD) may share clinical features with progressive multiple sclerosis (MS), so diagnostic overshadowing may occur. We hypothesized that cervical stenotic SDD is commoner in people with progressive MS, compared to controls. Methods: A retrospective case–control study of 111 cases (56 with progressive MS and 55 age‐ and sex‐matched controls) was conducted. Five types of cervical SDD (disc degeneration, posterior disc protrusion, endplate changes, canal stenosis and foraminal stenosis) were assessed objectively on magnetic resonance imaging using published scales. Multivariable regression analysis was performed. Results: Moderate‐to‐severe cervical spinal degeneration occurred more frequently in progressive MS, compared to controls. In multivariable regression, foraminal stenosis was three times more likely in progressive MS (odds ratio 3.20, 95% confidence interval 1.27, 8.09; p  = 0.014), and was more severe ( p  = 0.009). This finding was confirmed on retrospective evaluation of clinical radiology reports in the same population. Foraminal stenosis was twice as likely in progressive MS, compared to relapsing‐remitting MS. Conclusions: People with progressive MS are susceptible to foraminal stenosis. A higher index of suspicion for cervical SDD is required when appropriate neurological symptoms occur in the setting of progressive MS, to guide appropriate treatment or monitoring. Abstract : In a case control study, foraminal stenosis was more frequent amongst people with progressive multiple sclerosis versus age and sex matched control individuals. A higher index of suspicion for cervical spinal degenerative disease is required when appropriate neurological symptoms occur in the setting of progressive multiple sclerosis, to guide appropriate treatment or monitoring.